Święta Marcela – wzór odnowy duchowej w czasie kryzysu cywilizacyjnego - Konrad Keler (Wrocławski Przegląd Teologiczny)
In the second half of the 4th century, the Roman Empire went through deep crisis and was about to fall. The social and political institutions were decomposing and the moral and civil values were disappearing. The ancient Roman religion was almost gone and Christianity was still too frail to build up a new social and political order. It was a time of profound civilization crisis. In 410, Rome was besieged by the Visigoths led by Alaric. The barbarians looted and damaged the city and consequently destroyed the glorious past of the Roman Empire. But in time of crisis, there are always forces which do not remain passive but work out a new vision for society and give direction to renew and reinforce the vitality of the people. Not all approach historical events in a fatalistic way. In the declining years of ancient Roman civilization, there were people of vitality and vision who looked to the future with hope. Marcela (330–410), an aristocratic woman living in Aventine, began a community of women who decided to go against the main decadent stream of social life in Rome before its fall. Opposing the luxurious life style, the women lived with simplicity, an ascetic life and social commitment in favour of the poor. Marcela gradually formed a community of women who also dedicated themselves to study of the Scriptures. Some of the women knew well Greek and learned Hebrew. Experiencing the crises of spiritual values, Marcela pointed to the Word of God as a source of renewal and hope in the time of civilization’s collapse. The group used a strong intellectual approach to the given reality by reading and studying some of the famous classic writers and their contemporary thinkers. It was something exceptional in Rome that aristocratic women would look for education and lead a simple life. They were an interesting and unique group of women in ancient Rome with high intellectual ambition. After some time, Marcella got in touch with Hieronymus (Jerome), the secretary of Pope Damasus and later proclaimed Doctor of the Church. He helped these women to grow in Biblical spirituality. The group could be called the first Biblical Institute where study and meditation of Scripture were the priority. Later on, some of the women went with Hieronymus to the Holy Land, founded a monastery, and contributed in a significant way to the translation of the Bible into Latin which is known as Vulgate. We know the life and activity of Marcella mainly from the letters of Hieronymus. They indicate that she was an extraordinary woman for her time, the time of crisis and collapse of Roman civilization. Her story could inspire people of any epoch that has to pass through deep and intensive changes of social, cultural, and religious values.